2001
DOI: 10.1152/ajpcell.2001.281.4.c1188
|View full text |Cite
|
Sign up to set email alerts
|

Effects of protein tyrosine kinase and protein tyrosine phosphatase on apical K+ channels in the TAL

Abstract: We have previously demonstrated that the protein level of c-Src, a nonreceptor type of protein tyrosine kinase (PTK), was higher in the renal medulla from rats on a K-deficient (KD) diet than that in rats on a high-K (HK) diet (Wang WH, Lerea KM, Chan M, and Giebisch G. Am J Physiol Renal Physiol 278: F165-F171, 2000). We have now used the patch-clamp technique to investigate the role of PTK in regulating the apical K channels in the medullary thick ascending limb (mTAL) of the rat kidney. Inhibition of PTK wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
21
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 33 publications
2
21
0
Order By: Relevance
“…Because all ROMK iso- forms (1-3) have a C-terminal PTK phosphorylation motif, the reason for the isoform specificity of regulation by PTK likely involves the unique ROMK1 NH 2 terminus. Consistent with this view, the 30 pS K ϩ channel formed by ROMK2 and ROMK3 in TAL cells is not regulated by this kinase (33) and absence of high K stimulated 30 pS K ϩ channel activity in Romk1 Ϫ/Ϫ mice ( Table 6). The unique structural difference between ROMK1 and ROMK2 is that ROMK1 extended N-terminal with specific binding sites of hormones and protein kinase.…”
Section: Discussionsupporting
confidence: 63%
“…Because all ROMK iso- forms (1-3) have a C-terminal PTK phosphorylation motif, the reason for the isoform specificity of regulation by PTK likely involves the unique ROMK1 NH 2 terminus. Consistent with this view, the 30 pS K ϩ channel formed by ROMK2 and ROMK3 in TAL cells is not regulated by this kinase (33) and absence of high K stimulated 30 pS K ϩ channel activity in Romk1 Ϫ/Ϫ mice ( Table 6). The unique structural difference between ROMK1 and ROMK2 is that ROMK1 extended N-terminal with specific binding sites of hormones and protein kinase.…”
Section: Discussionsupporting
confidence: 63%
“…Several factors that have been shown to stimulate the 70-pS K ϩ channel include protein kinase A (PKA), the NO-cGMP-dependent pathway, and PTP (12,19,29). Therefore, we examined the effect of TNF on the 70-pS K ϩ channel in the presence of PKA inhibitors (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We previously observed that the 70-pS K ϩ channel is regulated by PTK and PTP (12). If the effect of TNF was the result of stimulation of PTP, which leads to enhancement of tyrosine dephosphorylation, inhibition of PTK should mimic the effect of TNF such that the effect of TNF on the 70-pS K ϩ channel activity should be absent in the presence of a PTK inhibitor such as herbimycin A.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations